Wrong about Japan : a father's journey with his son - Carey, Peter, 1943- (New York : Knopf, 2005)
The Booker Prize-winning author of Oscar and Lucinda describes how his shy young son's fascination with Japanese manga and anime led father and son on an intriguing odyssey to Tokyo, where they discover the intricacies of modern-day Japanese culture, from shitamachi and the Internet to kabuki and the samurai. The recipient of two Booker Prizes, Peter Carey expands his extraordinary achievement with each new novel and now gives us something entirely different. When famously shy Charley becomes obsessed with Japanese manga and anime, Peter is not only delighted for his son but also entranced himself. Thus begins a journey, with a father sharing his twelve-year-old's exotic comic books, that ultimately leads them to Tokyo, where a strange Japanese boy will become both their guide and judge. Quickly the visitors plunge deep into the lanes of Shitimachi into the weird stuff of modern Japan meeting manga artists and anime directors; painstaking impersonators called visualists, who adopt a remarkable variety of personae; and solitary otakus, whose existence is thoroughly computerized. What emerges from these encounters is a far-ranging study of history and of culture both high and low from samurai to salaryman, from Kabuki theater to the postwar robot craze. Peter Carey's observations are always provocative, even when his hosts point out, politely, that he is once again wrong about Japan. And his adventures with Charley are at once comic, surprising, and deeply moving, as father and son cope with and learn from each other in a strange place far from home. This is, in the end, a remarkable portrait of a culture whether Japan or adolescence that looks eerily familiar but remains tantalizingly closed to outsiders.
Keywords: Carey, Peter, -- 1943- -- Travel -- Japan; Fathers and sons -- United States; Fathers and sons -- Japan; Americans -- Japan; Japan -- Description and travel